Republik Islam Iran (Negara Modern Islam Syiah) - Amin, Surahman (Tasamuh: Jurnal Studi Islam, 2016)
Islam as a value system covers all aspects of human life. It not only sets the human relationship with God, but also regulates human relationships with the natural environment. Among the teachings of Islam there are also too teachings with regard to political life. Therefore, as a consequence of Muslims are required to strive to uphold the country, even though the Koran itself does not contain unequivocal proposition about how the concept of the country. In other words, that the state does not issue detailed instructions found in the arguments, particularly with regard to forms or models of government that must be executed within a country. Provisions of the country can only be found in the fundamental principles of a country that was built, it nevertheless forms a nation, whether royal or republics, is not a problem, the most important is how the elements and Islamic values capable applied in the country. The story of South Asian Muslims in an effort to build the country up to now is still being debated prolonged. How can the State of Iran? This article highlights the issue of Islam in the land of Iran, one of the Islamic civilizations